Implementasi Program Universal Health Coverage di Kota Pekanbaru Berdasarkan Peraturan Daerah Provinsi Riau Nomor 7 Tahun 2011 tentang Penyelenggaraan Jaminan Kesehatan - Mesra Noves (CV Rewang Rencang, 2021)
The Riau Provincial Government launched the Universal Health Coverage (UHC) program as of November 1, 2012, and has been regulated in Riau Provincial Regulation No. 7 of 2011 on the Implementation of Health Insurance. With this program, the community will get health services at First Level Health Facilities (FKTP) and services at 3rd class Hospitals managed by BPJS Kesehatan Riau Province. So it is expected that the UHC program in Riau Province can reduce the BPJS health deficit. But of course, in the implementation, there are obstacles that must be resolved by the Riau Provincial Government so that its implementation can be realized well for underprivileged communities. UHC is an innovation to provide health insurance for all communities that have not been covered by any health insurance. The innovation of the flagship program becomes the focus of research that can later be known the process and results provided so that it can be applied in other areas. The implementation of UHC is one of the concrete efforts made by the Riau Provincial Government to ensure public health services which is one of the criteria in the quadrant of the City Resilience Index (Riau Provincial Resilience Index). The presence of UHC itself is in line with the pillars of Riau province's resilience strategy that has been proclaimed by the Riau Provincial Government to reduce the risk of impact from disease outbreaks. UHC plays a role in the recovery of communities affected by the disease outbreak so that UHC does have a contribution in building the resilience of Riau Province but not much contribution has been made considering that the health sector has not been the main focus of the Riau Provincial Government.